Biodegradable poly(ethylene glycol-glycerol-itaconate-sebacate) copolyester elastomer with significantly reinforced mechanical properties by in-situ construction of bacterial cellulose interpenetrating network - Lisheng Tang; Yuanyuan Jin; Xiaoyan He; Ran Huang (Scientific Reports, 2024)
Abstract To address the concern that biodegradable elastomers are environmental-friendly but usually associated with poor properties for practical utilization, we report a star-crosslinked poly(ethylene glycol-glycerol-itaconate-sebacate) (PEGIS) elastomer synthesized by esterification, polycondensation and UV curing, and reinforced by bacterial cellulose (BC). The interpenetrating network of primary BC backbone and vulcanized elastomer is achieved by the “in-situ secondary network construction” strategy. With the well dispersion of BC without agglomeration, the mechanical properties of PEGIS are significantly enhanced in tensile strength, Young’s modulus and elongation at break. The reinforcement strategy is demonstrated to be efficient and offers a route to the development of biodegradable elastomers for a variety of applications in the future.